Effect of Polygoni Multifori Radix Extract on Menopause-Related Skin Aging - Kim, Eun-Suk; Kwon, Hye-Jin (International Journal of Psychosocial Rehabilitation, 2020)
Background/Objectives: The purpose of this study was to prepare an emulsion containing Polygoni Multifori Radix extract to help improve aging of skin menopausal women. Methods: The ovaries of 6–8-week-old SKH-1 hairless mouse were resected to induce menopausal aging, and Polygoni Multifori Radix extract were applied. This experimental group was compared with normal and natural aging controls. Findings: Histological observations of the epidermis demonstrated that the average thickness of epidermal lipid lamellae was 11.1%, the proportion of epidermal lipid lamellae was 5.73%, and the overall epidermal thickness was increased in the menopausal aging group. The observation of histological changes in the dermis also showed increased density of collagen and decreased amount of denatured elastic fibers. Improvements/Applications: Thus, Polygoni Multifori Radix extract was found to reduce the damage in skin tissues caused by menopausal aging and to suppress the wrinkles.